Cytotoxic and anti-migration properties of proteins from Pleurotus tuber-regium (Fr.) Singer and Termitomyces heimii Natarajan against human breast MDA-MB-231 and colon HCT-116 cancer cells / Erlina Abdullah - Erlina , Abdullah (2021)
The discovery and identification of new safe drugs that are specifically cytotoxic against cancer cells becomes an important target in cancer research. Increasing number of cancer deaths around the world are associated with metastasis and lack of specificity and effectiveness of current treatment. In developed countries such as Korea, Japan and China, mushrooms have been used for centuries for medicinal purposes against cancer. Numerous studies have reported the vast medicinal values of proteins isolated from mushrooms including anti-tumour and anti-cancer effects. The present study aims to investigate the potential of protein extracts from two Basidiomycetes species which are Pleurotus tuber-regium (Fr.) Singer (sclerotium and fruiting bodies) and Termitomyces heimii Natarajan (fruiting bodies) for anti-tumour effects as well as the mechanism of action against targeted cancer cells. Protein extraction from P. tuber-regium sclerotium, P. tuber-regium fruiting bodies and T. heimii fruiting bodies were conducted using ammonium sulphate precipitation technique. The protein fractions were determined based on different salt/ammonium sulphate concentration at 30%, 60% and 90%. All protein fractions of were assessed for cytotoxicity towards breast cancer cell lines (MDA-MB-231), colorectal cancer cell lines (HCT-116) and normal lung cell lines (MRC-5) in MTT assay. Potential protein extracts were identified based on the IC50 values and selectivity index (SI) on both cancer cells and normal cells. IC50 values are the extract concentrations required to inhibit half of the cells growth and SI values are the measure of safety level of drugs/compounds/extracts against normal cells as referred to cancer cells. Extracts with IC50 values less than 20 μg/ml are considered to be actively cytotoxic against target cells after 48-72 hours of incubation time, while SI value greater than 3 indicates potential selectivity of extracts or compounds towards cancer cells as compared to the normal cells. The most promising protein extract was PS60 of P. tuber-regium sclerotium with the lowest IC50 value (IC50=0.75±0.57 μg/ml) against MDA-MB-231 cells and with minimum cytotoxicity towards the normal lung cells (MRC-5) at SI value of 14. Cellular migration through tissues is one of the important events in metastasis. Ability of the mushroom protein extracts to inhibit such migration was evaluated using the scratch wound assay. Cytotoxicity and anti-migration (MCA) effects on cancer cells were best exhibited by PS60 of P. tuber-regium sclerotium with MCA reading ranging between 5.6581±0.2015 nm/h and 5.4142±0.6916 nm/h. The purification of PS60 (P. tuber-regium sclerotium) using LCMS-Q-TOF MS, had successfully isolated several different proteins, two of which are identified as kinesin-like protein and keratin type 1, cytoskeletal 10.PS60 was then further evaluated for apoptotic effects. PS60 was shown to exert cytotoxic effects associated with the induction of apoptosis and cell cycle arrest in MDA-MB-231 cells at G1/G0 and S-phase. In conclusion, PS60 protein of P. tuber-regium sclerotium have good potential to be developed into novel anti-tumour drugs against breast cancer.